Trainee Experiences in Industrial Retraining Programs: A Case Study - Burke, Ronald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The present study reports on the experiences of a group of 58 former Canadian Admiral employees who enrolled in academic upgrading or retraining programs sponsored by the Federal government. The emphasis is placed on their student role, and expectations for the future, since all were still in retraining.